An implementation of internet-connected indoor dust bin waste level monitoring system for office use / Mohammad Hafiz Ismail, Tajul Rosli Razak and Iman Hazwam Abd Halim - Ismail, Mohammad Hafiz; Razak, Tajul Rosli; Abd Halim, Iman Hazwam (UiTM Cawangan Perlis, 2019)
The paper discusses an implementation of an internet-connected monitoring system to optimize waste collection within office space environment. The implementation consists of four parts – the physical dustbin module, network, middleware and user interface. The implementation uses NodeMCU board with embedded microcontroller to sense and transmit waste level data to a middleware over 802.11 wireless network, while the middleware aggregate data from all registered dustbins within the office area. The aggregated data is then stored in a database server for further analysis. The web-based user interface is used to monitor the dustbins waste level as well as historical data report. This information is vital for waste level management planning and prediction. Additionally, a Technology Acceptance Model survey result has shown that the monitoring system is perceived to be easy to use and useful for office management in monitoring and managing their waste.